Numerical investigation of premixed methane-air flame in two-dimensional half open tube in the early stages. (15th July 2020) - Deng, Haoxin; Huang, Mingming; Wen, Xiaoping; Chen, Guoyan; Wang, Fahui; Yao, Zhifeng
Abstract: Premixed methane-air flame propagation in a two-dimensional half-open tube is studied using a computational fluid dynamic method. The flame is simulated using a laminar combustion model with simplified reaction mechanism. The first purpose of this work is to determine whether a 2D planar flame model can be used to predict flame propagation in a square-section tube. Another purpose is to investigate the evolution of the flame tip velocity after the flame skirt touches the wall, using the relationship between the flame surface area and the burnt gas volume growth. The simulation results show that the 2D planar flame model is not suitable for predicting the flame propagation in a square-section tube, and that the simulated position of the flame tip is reliable only when the flame skirt touches the wall. There is an approximate proportional relationship between the volume growth of burnt gas and the flame tip velocity even after the lateral flame touches the wall. The widely used equation for the relationship between burnt gas volume growth and flame surface area fails after the flame touches the wall, and then holds at several later times. The balance is broken by the continuous extinction of the flame skirt. Finally, we report the dimensionless time interval between when the flame skirt touches the wall and flame front inversion, as well as the dimensionless velocity of the flame skirt. There are some differences between the values of the dimensionless time interval in 2D planar tubes and in 3D cylindrical tubes.